(3GdeaVd Ydi GdeaVd aj OQGjI GdeaUds - (3YHO GdhGMO Hf YHO GdcQje Hf Nda GdCfUGQj GdRedcGfj , CHhGdecGQe ceGd GdOjf , J (B651 (3g`s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3aUd(B: (3bGd SjHhjg hgPg MLL oSeYJ ef GdYQH jbhdhf(B: (3Gddge VHYG hPjHG s
(3BNQgG (B:s
(3dCf HGH ThjJ hWhjJ CcKQ ef HGH ahg hNhg hGdYde YfO Gddg s
(3GdeaUd ddReNTQj GdeJhai (B538s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs